The Impact of COVID-19 Restrictions on Victim Advocacy Agency Utilization Across Pennsylvania - Wright, Elizabeth N. (Journal of family violence, 2022)
This brief report highlights the impact of the COVID-19 restrictions on the utilization of Victim Advocacy Agencies’ (VAAs’) services across Pennsylvania, using VAA utilization data from 2019–2020. VAA utilization data in this report were collected from 2019–2020 by the Pennsylvania Coalition Against Rape (PCAR). VAA utilization data were anchored to COVID-19 restriction timelines, defined by the Pennsylvania Office of the Governor. For each month, a percent change in VAA utilization (e.g., Jan 2020 utilization compared to Jan 2019 utilization) was calculated. A one-way ANOVA was run to assess whether the association between restriction phase and percent change in overall VAA utilization from 2019 to 2020 was statistically significant. A substantial decrease in VAA utilization was observed once lockdown restrictions were enacted, as well as a sustained decrease in utilization between 2019 and 2020. When restrictions were eased, an increase in service utilization was noted. This pattern of findings held for the three variables assessed: hotline utilization, new client, and medical accompaniments for FREs per month. The one-way ANOVA confirmed a statistically significant decrease in overall VAA utilization when comparing the most severe COVID-19 related restrictions to both pre-COVID and less severe restrictions. A variety of barriers (e.g., financial instability, loss of childcare, technology access, chronic physical proximity to abuser, hospital visitation restrictions, fears of contracting the virus) may result in decreased utilization of VAA services. Future research should investigate the relevance of potential causal mechanisms behind VAA utilization to help inform intervention approaches.